Komunikasi Politik Kiai Dalam Pemilihan Umum Tahun 2019 - Mushthofa Misyuniarto, Khoirul (Jurnal Ilmu Komunikasi, 2020)
This study examines the political communication strategy carried out by Kiai as a boarding school caretaker in the General Election. The purpose of this study is to describe the political communication strategy carried out by Kiai Syafik Rofi’i, caretaker of the Salafiyah Syafi’iyah Islamic Boarding School in Bangkalan Regency, East Java Province in the 2019 General Election. This study uses a qualitative descriptive method with a case study approach. The results showed that the political communication strategy being implemented was political negotiation among kiai in Islamic boarding schools in Bangkalan Regency. In addition, political communication uses the strategy of a campaign winning team or success team, and also uses the media as a channel for delivering messages to provide understanding and influence public opinion.